Flora Colonization and Oral Glucose Levels During the Early Postnatal Period in High-Risk Newborns - Young-mee Ahn (Child Health Nursing Research, 2016)
Purpose: A longitudinal study was conducted to explore flora colonization and oral glucose high-risk newborns during the first 7 days after birth. Methods: Oral secretions of hospitalized newborns were obtained for microbial cultures and glucose test at days 1-7 after birth. Results: Among the total 112 newborns, 40% were girls and 73% were premature. Mean gestational age was 34.4±3.2 weeks and weight was 2,266±697.5 grams. The most common flora included Streptococcus (28.2%), Methicillin-resistant Staphylococcus aureus (MRSA, 10.9%), Staphylococcus (6.0%), and Coagulase- Negative Staphylococcus (CNS, 4.0%). The average oral glucose level was 29.2±23.0 mg/dL~58.2±39.5 mg/dL. Newborns with higher oral glucose than serum (crude odds ratio [ORc] =1.75; 95% confidence interval [CI] =1.03-2.97), phototherapy (ORc=3.30; 95% CI=2.29-4.76) and prone position (ORc= 2.04; 95% CI=1.13-3.69) were more likely to be colonized. Having oral tubes (ORc=0.42; 95% CI=0.29-0.59), parental nutrition (ORc=0.21; 95% CI=0.13-0.32) and antibiotics (ORc=0.51; 95% CI=0.36-0.73) had protective effects. For oral glucose statistical significances existed on time effect among newborns with Streptococcus (F=9.78, p=.024), MRSA (F=7.60, p=.037) or CNS (F=11.15, p=.019) and interaction between time and colonization among newborns with all of four flora (F=2.73, p=.029) or colonization with only Staphylococcus (F=2.91, p=.034). Conclusion: High-risk newborns develop flora colonization at an early period of life. Their clinical features were associated with types and time of oral flora colonization. They need close monitoring and multifaceted intervention to improve oral environment and infection control.